Beyond the usual challenges, a case of LV summit PVCs ablation in child with ASO for D-TGA - Mahmoud Abdelfattah; Eslam Ahmed; Ahmed Nasr; Mostafa El Husseny; Omnia Kamel (BMC Cardiovascular Disorders)
Abstract Premature ventricular contractions (PVCs) are a common finding in patients with surgically repaired congenital heart defects including transposition of the great arteries (D-TGA). While often asymptomatic, PVCs can sometimes lead to palpitations, dyspnea, and hemodynamic compromise, requiring therapeutic intervention. The arterial switch operation is the preferred treatment for D-TGA, but these patients have a 2% incidence of ventricular arrhythmias and 1% incidence of sudden cardiac death post-operatively. Though radio-frequency ablation is an effective option for treating outflow ventricular arrhythmias, little data is available on its use in the post-arterial switch D-TGA population. This case report describes a successful catheter ablation of frequent PVCs originating from the left ventricular summit region in a 9-year-old child with a history of arterial switch repair for D-TGA and frequent monomorphic PVCs, highlighting the challenges and considerations in managing ventricular arrhythmias in this complex anatomical setting.